Chemotaxis Movement and Attachment of Agrobacterium tumefaciens to Phalaenopsis violacea Orchid Tissues: An Assessment of Early Factors Influencing The Efficiency of Gene Transfer - Sreeramanan Subramaniam,; Vinod Balasubramaniam,; Ranjetta Poobathy,; Sasidharan Sreenivasan,; Xavier Rathinam, (Tropical Life Sciences Research, 2009)
An early step in the Agrobacterium-mediated transformation of Phalaenopsis violacea orchid was investigated to elucidate the plant-bacterium interaction. Directed movement in response to chemical attractants is of crucial importance to Agrobacterium tumefaciens strains. Chemotaxis of A. tumefaciens strains (EHA 101 and 105) towards wounded orchid tissues has been studied by using swarm agar plates. The results obtained indicate a minor role for chemotaxis in determining host specificity and suggest that it could not be responsible for the absence of tumourigenesis in P. violacea orchid under natural conditions. The spectrometric GUS and green fluorescent protein (GFP) assays provided information on the amount of inoculated A. tumefaciens that effectively bound to various orchid tissues. It can be concluded that, at least during the two early steps of interaction, A. tumefaciens appears to be compatible with P. violacea, indicating a potential basis for genetic transformation. Peringkat awal transformasi perantaraan Agrobakterium di dalam orkid Phalaenopsis violacea telah dijalankan bagi menyiasat interaksi diantara tumbuhan dengan bakteria. Pergerakan berarah berdasarkan tindakbalas tarikan kimia merupakan kepentingan utama bagi jenis Agrobakterium tumefaciens. Kemotaksis A. tumefaciens (EHA 101 dan 105) terhadap tisu orkid yang dilukakan telah dikaji dengan menggunakan swarm agar plates. Keputusan yang diperolehi menunjukkan peranan kemotaksis adalah kecil dalam menentukan pengkhususan penerima dan ini menunjukkan ia tidak bertanggungjawab bagi ketiadaan tumoregenesis pada orkid P. violacea dalam keadaan semulajadi. Ujian spektrofotometrik GUS dan GFP memberikan informasi mengenai jumlah A. tumefaciens yang diinokulasi melekat dengan efektif pada pelbagai jenis tisu orkid. Oleh itu ia boleh disimpulkan bahawa sekurang-kurangnya pada dua peringkat awal interaksi, A. tumefaciens didapati serasi dengan P. violacea dan ini merupakan asas yang berpotensi bagi pembangunan genetik transformasi.